Correction: Anatomy of the sacroiliac joint with relation to the lumbosacral trunk: Is there sufficient space for a two-hole plate? - Michał Kułakowski; Karol Elster; Paweł Reichert; Aleksandra Królikowska; Joanna Jerominko; Paweł Ślęczka; Magdalena Grzonkowska; Michał Szpinda; Mariusz Baumgart (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0292620.].